Implementasi Manajemen Strategi di Bank Syariah dalam Menghadapi Tantangan Pandemi COVID-19 - Pramudita, Defrangga Piyu (Maliki Interdisciplinary Journal, 2025)
The purpose of writing this article is to find out the implementation of strategic management in sharia banks in facing the challenges of the COVID-19 pandemic. The method used in this research uses the literature study method, namely a research method carried out by collecting, analyzing and interpreting information from various reading sources, such as books, scientific journals, articles, research reports and other sources relevant to the topic at hand. being researched. The results of this research are that the COVID-19 pandemic has dealt a significant blow to the performance of sharia banking in Indonesia, however, this sector shows quite good resilience. Despite facing challenges in terms of liquidity, solvency and profitability, Islamic banks have succeeded in maintaining the BOPO ratio below 100%. To face post-pandemic challenges, Islamic banks need to make various adaptive efforts, such as financing restructuring, accelerating digitalization, optimizing liquidity, and strengthening risk management. Apart from that, increasing customer financial literacy, collaborating with fintech, and strengthening social roles are also keys to the success of Islamic banks in adapting to market changes and ensuring sustainable growth in the future.